Is biomass burning always a dominant contributor of fine aerosols in upper northern Thailand? - Wenhuai Song; Yan-Lin Zhang; Yuxian Zhang; Fang Cao; Martin Rauber; Gary Salazar; Sawaeng Kawichai; Tippawan Prapamontol; Sönke Szidat (Environment International, 2022)
Biomass burning (BB) is an important contributor to the air pollution in Southeast Asia (SEA), but the emission sources remain great uncertainty. In this study, PM2.5 samples were collected from an urban (Chiang Mai University, CMU) and a rural (Nong Tao village, NT) site in Chiang Mai, Thailand from February to April (high BB season, HBB) and from June to September (low BB season, LBB) in 2018. Source apportionment of carbonaceous aerosols was carried out by Latin Hypercube Sampling (LHS) method incorporating the radiocarbon (14C) and organic markers (e.g., dehydrated sugars, aromatic acids, etc.). Thereby, carbonaceous aerosols were divided into the fossil-derived elemental carbon (ECf), BB-derived EC (ECbb), fossil-derived primary and secondary organic carbon (POCf, SOCf), BB-derived OC (OCbb) and the remaining OC (OCnf, other). The fractions of ECbb generally prevailed over ECf throughout the year. OCbb was the dominant contributor to total carbon with a clear seasonal trend (65.5 ± 5.8 % at CMU and 79.9 ± 7.6 % at NT in HBB, and 39.1 ± 7.9 % and 42.8 ± 4.6 % in LBB). The distribution of POCf showed a spatial difference with a higher contribution at CMU, while SOCf displayed a temporal variation with a greater fraction in LBB. OCnf, other was originated from biogenic secondary aerosols, cooking emissions and bioaerosols as resolved by the principal component analysis with multiple liner regression model. The OCnf, other contributed within a narrow range of 6.6 %-14.4 %, despite 34.9 ± 7.9 % at NT in LBB. Our results highlight the dominance of BB-derived fractions in carbonaceous aerosols in HBB, and call the attention to the higher production of SOC in LBB.